Legal Protection Of Intellectual Property Rights In Indonesia Civil Law : Perspectives And Challenge In The Digital Era - Prihatin, Lilik; Listyowati, Maria Yosepin Endah (Leges Privatae, 2024)
This research explores the legal protection of Intellectual Property Rights (IPR) in Indonesia’s civil law, focusing on the perspectives and challenges in the digital era. With the rapid advancement of digital technology, the landscape of intellectual property has significantly evolved, creating both opportunities and risks. The study examines the existing legal frameworks that safeguard IPR in Indonesia, analyzing the effectiveness of current laws in protecting creators' rights amidst technological advancements. The research identifies key challenges such as the inadequacy of regulations to keep up with digital innovations, the rise of online piracy, and difficulties in enforcement. By comparing Indonesia's IPR protection system with global practices, this paper also suggests improvements and recommends policy adjustments. The findings underscore the importance of adapting the legal infrastructure to address the complexities of the digital era, ensuring better protection for creators, and promoting innovation. The study highlights the critical role of government agencies, public awareness, and international collaboration in reinforcing IPR safeguards.